Projected Customer Growth Rate of Hospital Pharmacy Installation in Blitar from 2021 to 2023 - Wahyuningtiyas, Triya; Purwidyaningrum, Ika; Wijayanti, Tri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Quality of pharmaceutical services can be measured by the performance of the Blitar General Hospital Pharmacy Installation which focuses on customer growth rates. This study aims to determine the growth rate of outpatient and inpatient customers of the Blitar General Hospital Pharmacy Installation from 2021 to 2023. This research uses a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and document studies, which were then analyzed using a qualitative approach. The results showed that the total customer growth rate increased over time; in 2021, there were 12,786 customers; in 2022, there were 44,833 customers; while in 2023, there were 58,850 customers